Penguatan Pasar UMKM melalui Digitalisasi Manajemen Sumber Daya Manusia dan Tata Kelola Produk - Rinintha Parameswari; Fredy Perdana Putra; Rudiyanto Rudiyanto; Darwin Tantowi; Virdi Gunawan; Nasrani Septin Kristiani Gulo (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This community service program aims to enhance the competitiveness and market access of Micro, Small, and Medium Enterprises (MSMEs) through the implementation of digitalization in human resource management and product governance strategies. The activities were carried out using a participatory approach involving MSME actors, lecturers, and students to ensure program sustainability. The implementation methods included identifying partner needs, planning activities, training on the use of digital applications for HR management, conducting market-oriented product management workshops, and providing intensive field mentoring. The results showed a significant improvement in participants’ digital skills, particularly in utilizing technology for workforce management and business operations. Additionally, participants demonstrated increased creativity in product packaging and presentation, making their products more attractive to consumers. The program also fostered the emergence of adaptive local leadership and raised collective awareness of the importance of digital transformation in business development. Overall, this activity demonstrates that integrating digitalization in HR management with effective product governance can strengthen MSMEs’ market position and contribute to accelerating sustainable economic transformation.